The Motivation of Future Teachers Learning: Psychological Parameters - Paliukaitė, Neringa (Acta Paedagogica Vilnensia, 2005)
The growth in mass of the higher education, when more and more members of society begin to satisfy their educational needs, encourages a student to be looked at as a subject, learning independently. Within this context of learning paradigm an initial motivation of student’s learning is necessary. The article analyses the motivation of students’ learning in VPU in various specialities (psychology and Lithuanian philology). By referencing to the most frequently used conceptions the concept of motive, motivation is discussed. Psychological parameters of the motivation of learning are accentuated: aspirations, value orientations, motives of further learning. The data of the research revealed that the majority of VPU students do not have inner motivation to work a pedagogical work. The aim of the research - to define the motivation of students learning in VPU by referencing to the accentuated psychological parameters of motivation of learning (aspirations, value orientations, motives of further learning). Investigatives: the investigation had been carried out in Vilnius Pedagogical University, in the faculties of pedagogy - psychology and Lithuanian philology. 340 investigatives participated in the research. 181 (53,23 proc.) investigatives were students of Lithuanian philology, 159 (46.76 proc.) – students of psychology. The technique of the research: during the quantitative research Beresnevičienė’s (1995) questionnaire was used. The research of VPU students indicated that the majority of students of this higher school do not have inner motivation to work a pedagogical work, they do not want to be teachers. The data of the research revealed that VPU students are motivated to study mainly by the wish to perfect themselves as personalities and accidental circumstances. Only 22,6 per cent of the respondents after having finished their studies would like to work as teachers of the speciality. The future psychology teachers especially lack pedagogical singleness. After their studies, VPU students would like to work as psychologists / lituanists (39,7 percent), least of the respondents would like to have their own business (5 percent). 50 percent of students relate further studying with postgraduate studies and only 9,7 percent would like to engage in self-education. VPU students gave the highest grades to these values: health, concord and love within the family, possibility to work a favourite job, possibility to grow as a personality; lowest grades – to possibility to rule others.